Effect of Gratitude, Forgiveness, and Social Support on Retiree Well-being with Self-efficacy as a Mediator Variable - Qodariah, Siti; Ancok, Djamaluddin; Wulan, Ratna; Dewi, Mahargyantari Purwani (Universitas Islam Bandung, 2023)
Many psychological problems arise when facing retirement due to unpreparedness during this period. Unpreparedness is commonly triggered by their fears of being unable to meet primary and secondary needs. Physical issues such as retirement health are essential, but paying attention to psychological problems is also necessary. Research on the well-being of retirees needs to be done to see what factors influence both internally and externally. This study aims to test the retirement well-being model in terms of such aspects as gratitude, forgiveness, and social support mediated by self-efficacy. This study used the structure equation model (SEM) approach with a sample of 220 retirees aged at least 55 through a convenience sampling technique. The data was collected in Bandung and its surroundings for six months, from August 2019 to March 2020, through well-being, gratitude, forgiveness, social support, and self-efficacy scales. The results of the research model tested have a good fit with empirical data and meet the goodness of fit requirements. There is a direct influence of gratitude, social support, and self-efficacy on well-being. There is an indirect effect of social support on well-being through self-efficacy. The value of the indirect effect is smaller than the direct effect, meaning that self-efficacy is not a good mediator variable for social support for well-being. In conclusion, most retirees experience well-being due to social support from their environment and their gratitude and self-efficacy. The well-being of retirees can be increased by appreciation, having social support from the environment, and having confidence in one's ability to deal with problems.